Hospitalized patients with isolated distal deep vein thrombosis: anticoagulation therapy or not? - Luo, Xiaolin; Zhang, Liying; Hou, Changchun; Li, Pengda; Wu, Shaofa; Wang, Zebi; Yang, Enpu; Cui, Yun; Sun, Ning; Yu, Yang; An, Zhixia; Jin, Jun; et al. (Thrombosis journal, 2022)
Background Isolated distal deep vein thrombosis (IDDVT), a disease frequently detected in hospitalized patients, can progress to proximal deep vein thrombosis (PDVT) and pulmonary embolism (PE). Here, we evaluated the effects of anticoagulation in hospitalized IDDVT patients. Methods We conducted a retrospective study in our hospital and enrolled hospitalized IDDVT patients diagnosed by compression ultrasonography (CUS) from January to December 2020. Participants were divided into anticoagulation (AC) and non-anticoagulation (non-AC) groups. After propensity score matching (PSM), multivariate Cox regression analyses were performed to assess whether anticoagulation was associated with PDVT/PE, and all-cause mortality. Results A total of 426 IDDVT inpatients with CUS follow-up were screened from 1502 distal DVT patients and finally enrolled. The median age was 67 years with 51.4% males and 15.5% cancer patients. The median follow-up was 11.6 months. There were 288 and 138 patients treated with or without anticoagulants, respectively. Patients in the non-AC group had less body mass index and more comorbidities. Patients in the AC group were treated with rivaroxaban or dabigatran (52.1%), low molecular weight heparin (42.7%), and warfarin (5.2%). The PSM generated 111 pairs of well-matched IDDVT patients with or without anticoagulation. The Kaplan-Meier analysis demonstrated that neither the incidence of PDVT/PE (5.4% vs. 2.7%, log-rank p = 0.313) nor all-cause mortality (27.9% vs. 18.9%, log-rank p = 0.098) was significant different between groups. Anticoagulation was not associated with PDVT/PE and all-cause mortality in the multivariable Cox regression analyses using the matched cohorts. The main risk factors for all-cause mortality were age, malignancy history, BMI, sepsis, heart failure, and white blood cell (WBC) count. Conclusions In hospitalized IDDVT patients, the thrombosis extension rate to PDVT/PE was low. Anticoagulation did not reduce the incidence of thrombosis extension of IDDVT and was not associated with all-cause mortality. Keywords: Anticoagulation, Isolated distal deep vein thrombosis, Inpatients, Mortality, Pulmonary embolism, Proximal deep vein thrombosis